2016
DOI: 10.2147/ott.s96535
|View full text |Cite
|
Sign up to set email alerts
|

Twist2 promotes kidney cancer cell proliferation and invasion by regulating ITGA6 and CD44 expression in the ECM-receptor interaction pathway

Abstract: Twist2 is a member of the basic helix-loop-helix (bHLH) family and plays a critical role in tumorigenesis. Growing evidence has proven that Twist2 is involved in tumor progression; however, the role of Twist2 in human kidney cancer and its underlying mechanisms remain unclear. Real-time polymerase chain reaction and Western blot analysis were used to detect the expression of Twist2 in kidney cancer cells and tissues. Cell proliferation, cell cycle, apoptosis, migration, and invasion assay were analyzed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…Currently, there are literature reports on using FAK as a novel potential biological target to investigate targeted therapy of NSCLC ( 39 , 40 ). The ECM-receptor interaction signalling pathway mediates the expression of enriched genes and regulates functions of these genes to promote tumour cell proliferation and migration and participate in tumour metastasis and infiltration ( 41 , 42 ). In NSCLC unrelated to smoking, the ECM-receptor interaction signalling pathway plays a critical role ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are literature reports on using FAK as a novel potential biological target to investigate targeted therapy of NSCLC ( 39 , 40 ). The ECM-receptor interaction signalling pathway mediates the expression of enriched genes and regulates functions of these genes to promote tumour cell proliferation and migration and participate in tumour metastasis and infiltration ( 41 , 42 ). In NSCLC unrelated to smoking, the ECM-receptor interaction signalling pathway plays a critical role ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, after binding with HA, CD44 protein interacts with TGF-β receptor I, and enhance TGF-β1 signaling because the matrix metalloproteinase-9 (MMP-9), bounded with this complex, cleave pro-TGF-β1 into its active form 36 . At the same time in RCC (in Caki-1, Caki-2, ACHN, and 786-0) cells CD44 expression was shown to be up-regulated by Twist2 -member of the basic helix-loop-helix (bHLH) family 40 . In breast cancer model it has been shown that HIF-1α as a regulator of CD44 that increased the number of CD44 molecules and the percentage of (variant exons v6 and v7/8) CD44 positive cells is higher in cancer cells in hypoxia 41 , which might also be true for RCC that is known to harbor VHL mutations.…”
Section: Discussionmentioning
confidence: 95%
“…The above signaling pathways, particularly ECM-receptor interaction pathway, are closely related to the pathogenesis of VRL. The ECM-receptor interaction pathway plays a crucial role in breast cancer and kidney cancer [25,59], and miRNAs have been shown to regulate this pathway [60]. The KEGG pathway analysis showed substantial overlap among the signal transduction pathways of target gene sets involved in cancer transcriptional dysregulation pathway, proteoglycan, and cancer pathways, suggesting that these pathways may be closely related to cancers including VRL.…”
Section: Discussionmentioning
confidence: 99%